PECULIARITIES OF CADASTRAL MAPPING OF UNDERGROUND SPACES (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The article proposes that cadastral mapping of underground spaces should be undertaken both manually and with instruments. It is preferable to use manual methods during cadastral registration work, while during the work for State Registration of Rights instruments should be used.
Keywords: underground spaces; cadastral mapping; cadastral registration; manual methods; instrumental methods